Three column stabilization through posterior approach alone: Transpedicular placement of distractable cage with transpedicular screw fixation - Ayberk, Giyas; Ozveren, Mehmet Faik; Altundal, Naci; Tosun, Hakan; Seckin, Zekai; Kilicarslan, Kasim; Kaplan, Metin (Japan Neurosurgical Soc, 2008)
The combination of anterior and posterior instrumentation provides the most stable repair for burst fractures of the thoracolumbar spine. However, the use of both approaches on a trauma patient may increase morbidity. Stabilization of three columns through only one approach can provide an effective outcome. We treated eight patients with burst fracture involving the thoracic or lumbar vertebrae by the application of anterior and posterior stabilization instruments through only the posterior approach. The desired stabilization was obtained in all patients. The advantages are the absence of the risks of the anterior approach, facilitation of the placement of anterior and posterior stabilization devices through only one approach, preserving the unity of the anterior longitudinal ligament, the effect of the anterior corpus in preventing displacement of the cage, application of compression on the pedicle screw system to both decrease the kyphosis angulation due to collapse of vertebra and to help the stabilization of the cage, repair of the dural tears at the posterior side, prevention of cage displacement by distraction and thus leaning on the endplates, and ease of performance by a neurosurgeon alone.
Keywords: corpectomy; intercorporal distractable cage; posterior approach